Phase I Study of Subcutaneous Rituximab Hyaluronidase Combined With CHOP Chemotherapy for the Treatment of Diffuse Large B-Cell Lymphoma in Uganda - Manoj P. Menon; Henry Ddungu; Kelvin R. Mubiru; Scott V. Adams; Jacqueline Asea; Rosemary Namagembe; Prossy Namuli; Joyce Kambugu; Andrea M.H. Towlerton; Camille Puronen; Thomas S. Uldrick; Jackson Orem; et al. (JCO Global Oncology)
PURPOSEPatients with diffuse large B-cell lymphoma (DLBCL) who are treated in low-resource settings have inferior outcomes compared with those in high-resource settings. Rituximab, an anti-CD20 monoclonal antibody, when combined with chemotherapy, improves overall survival (OS) for DLBCL. However, in part due to the limited availability of infusion centers in low-resource countries, rituximab is rarely used. Subcutaneous rituximab (sqR) is a potential solution; however, its safety and efficacy have not been tested in low-income countries.METHODSThis open-label phase I study enrolled patients 18 years or older with newly diagnosed DLBCL. The first cohort (n = 6) received intravenous rituximab plus CHOP. This cohort received sqR for subsequent cycles. The second cohort (n = 12) received sqR plus CHOP for all cycles. Safety and tolerability were evaluated; secondary outcomes included response rates and treatment completion.RESULTSBetween October 25, 2019, and October 7, 2022, 18 patients, with a median age of 36.5 years, were enrolled; 10 were male, and 10 presented with advanced-stage disease. The most common hematologic toxicity was neutropenia (n = 9, 50%). Fifteen of the 18 participants completed treatment; 14 (93.3%) patients achieved a complete response, and one patient (6.7%) had a partial response. The OS and progression-free survival (PFS) at 12 months were 83% (95% CI, 68 to 100) and 67% (95% CI, 48 to 92), respectively. The OS and PFS at 24 months were 66% (95% CI, 47 to 92) and 67% (95% CI, 48 to 92), respectively.CONCLUSIONAs demonstrated in other parts of the world, sqR together with CHOP was safe, well-tolerated, and efficacious among Ugandan patients with DLBCL. The very high OS rates are nearly double those of historical controls and comparable with outcomes expected in resource-rich settings. This study demonstrated the feasibility, safety, and efficacy of sqR-CHOP, increased the research infrastructure in Uganda, and will improve care in other resource-limited settings.